2017
DOI: 10.4314/ijs.v19i2.22
|View full text |Cite
|
Sign up to set email alerts
|

Utility of pollution indices in assessment of soil quality around Madaga gold mining site, Niger state, North-central Nigeria

Abstract: The quality of soil in the vicinity of Madaka mining sites were investigated in this study using Environmental Pollution Indices. Geological mapping of the study area indicated that the area was dominated by schist and granite. The static water level measurement revealed a westward groundwater flow direction which also coincides with the regional structural trend of the area. Laboratory analyses of soil and stream sediment were carried out in National Geosciences Research Laboratory Kaduna. The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
(28 reference statements)
1
11
1
Order By: Relevance
“…The highest levels of Pb and Cd in the study where 808.16 and 116.91 mg/kg respectively. A study on the environmental impact of artisanal gold mining in Luku, Minna, Niger State, Nigeria has also been reported [17] The results shown in the present study as well as those reported in the literature [16] show that the soil samples from Maigiro, Kawo in Rafi LGA are heavily contaminated by Pb and Cd. Contamination in Madaka was found to be lower.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The highest levels of Pb and Cd in the study where 808.16 and 116.91 mg/kg respectively. A study on the environmental impact of artisanal gold mining in Luku, Minna, Niger State, Nigeria has also been reported [17] The results shown in the present study as well as those reported in the literature [16] show that the soil samples from Maigiro, Kawo in Rafi LGA are heavily contaminated by Pb and Cd. Contamination in Madaka was found to be lower.…”
Section: Resultssupporting
confidence: 81%
“…In a study on the utility of pollution indices in the assessment of soil quality around Madaga gold mining site, Niger State, North-Central Nigeria, it was reported that the soil around the gold mining sites is seriously polluted by mercury, cadmium and lead, moderately polluted with arsenic, lightly polluted with iron and copper and very lightly polluted with manganese, zinc, nickel and cobalt in the order of Hg > Cd > Pb > As > Fe > Cu > Mn > Zn > Ni > Co [16]. The highest levels of Pb and Cd in the study where 808.16 and 116.91 mg/kg respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Kabas et al (2017) indicated that under acidic conditions bioavailability of metals increases therefore accentuating their effect in plants. Comparatively, the pH and nutrient levels in soil are lower than other abandoned mine sites in China, Portugal, Poland and Nigeria (Guo et al, 2019;Amadi et al, 2017;Kasowska et al, 2018;Pratas et al, 2005). The low nutrient level at study area is known to impair optimal growth and development of plants (Mensah, 2015).…”
Section: Discussionmentioning
confidence: 94%